Neuroprotective roles of flavonoid “hispidulin” in the central nervous system: a review - Mustapha, Saeed; Magaji, Rabiu Abdussalam; Magaji, Mohammed Garba; Gaya, Ibrahim Bako; Umar, Baraka; Yusha’u, Yusuf; Daku, Abubakar Bishir; Chiroma, Samaila Musa; Jaafar, Aliyu; Mehat, Mohamad Zulfadli; Mat Taib, Che Norma; Moh’d Moklas, Mohamad Aris (Mashhad University of Medical Sciences, 2024)
Interest in naturally occurring phytochemicals has been on the increase, they are believed to reduce the risk of brain disorders. Hispidulin (HN) is a phenolic flavonoid compound with various pharmacological and biological effects on the central nervous system. It belongs to the flavone class of flavonoids. It can be found in different plant materials, especially fruits and vegetables. The literature used in this review was collected from credible scientific databases including ScienceDirect, Scopus, PubMed, Google Scholar, and Hindawi without time restriction, using relevant keywords, such as HN, brain, central nervous system, flavonoids, and flavones. HN was discovered to possess pro-apoptotic properties, act as an antioxidant, inhibit cytokine production and toll-like receptor 4 expression, as well as impede nuclear factor kappa beta and mitogen-activated protein kinase B. HN was also found to inhibit lipid peroxidation in vitro and reduce brain edema in mice. These pharmacological potentials suggest that HN is a promising candidate for neuroprotection in CNS disorders like depression and epilepsy. This review provides an update on the scientific literature concerning how these activities could help provide various forms of neuroprotection in the CNS. Additional experimental data on the effects of HN in models of neurological disorders and neuroprotection should be explored further. Based on the current study, HN is a promising candidate for neuroprotection of the CNS.